Threatened butterflies: a new subspecies of Neptis manasa Moore, 1858 from Hainan Island (Lepidoptera, Nymphalidae) - Lang, Songyun; Xue, Dayong; Han, Hongxiang (Zootaxa, 2009)
Neptis manasa Moore, 1858, belonging to the tribe Neptini (Nymphalidae: Limenitidinae), is distributed along the northern border of the Oriental Region. So far, four subspecies have been recorded: N. m. manasa Moore, 1858 (North India to north Thailand), N. m. antigone Leech, 1890 (South China), N. m. narcissina Oberthür, 1906 (Northwest Yunnan, China) and N. m. shinkaii Koiwaya, 1996 (Southeast Tibet, China). N. manasa is very rare compared with most species of the genus Neptis. Restricted only to virgin forests, its habitats have been destroyed by the economic developments of China and neighbouring countries. Thus, N. manasa is likely to be threatened by losing its required habitats. Gu (1997) first recorded N. manasa from Hainan Island and considered the insular race as the nominate subspecies. We studied two N. manasa specimens collected in the early 1980s by Mr. Gu from Hainan and found that the insular race is quite different from all known subspecies based upon external features and male genitalia. The purpose of this paper is to describe the insular race from Hainan Island as a new subspecies and bring attention to its probably threatened status.